Advances in Fetal Imaging - Rubesova, Erika; Barth, Richard A. (American Journal of Perinatology, 2014)
While ultrasound (US) has been a part of prenatal care for almost 40 years, technical progress over the last two decades has resulted in improved image quality and detection rate of congenital anomalies. The past 15 years have also seen the expansion of three-dimensional (3D) US, providing enhancements over with 2D US, and more realistic images of babies to parents and providers. Fetal magnetic resonance imaging (MRI) was first performed over 30 years ago, and has undergone major technical improvement over the past 15 to 20 years. Fetal MRI complements US by providing better visualization in the fetus when US is limited such as in oligohydramnios or severe maternal obesity. It offers a larger field of view and better tissue contrast than US and is not limited by shadowing from osseous structures. However, MRI has a limited resolution compared with US, is less readily available, and more expensive. While indications for fetal MRI have been clearly established for some abnormalities, such as neurological anomalies, other indications especially for fetal body imaging are not as clearly defined. In this article, we discuss recent developments in fetal MRI and 3D US and their common and newest indications.
Keywords: fetal; imaging; fetal MRI; 3D US